Cemento-ossifying fibroma of the jaw - David B. Kamadjaja (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Cemento-ossifying fibroma is a benign neoplasm characterized by replacement of normal bone by fibrous tissue and varying amounts of newly formed bone or cementum-like material, or both. The cemento-ossifying fibroma has caused considerable controversy because of confusion regarding terminology and the criteria for its diagnosis. In addition, the cemento-ossifying fibroma often shows variations in clinical, radiographic, and histopathologic features, hence require different treatment options. Purpose: This paper attempts to elaborate the classification and terminology of cemento-ossifying fibroma of the jaw, the clinical characteristic, radiographic, and histopathologic features, the different tumor behaviors, and the surgical treatment modalities required. Case: Two patients diagnosed with cementifying fibroma and two patients with ossifying fibroma were reported, presenting their clinical presentation, diagnostic imaging, and histopathology reports, as well as their surgical treatments. Classifications of fibro-osseous lesion of the jaws and characteristics as well as variations in several aspects of cemento-ossifying fibroma of the jaws are discussed. Conclusion: The diagnosis of cemento-ossifying fibroma of the jaw can be established quite consistently based on clinical, radiographic, and microscopic features. However, these tumors may exhibit variations in their neoplastic behaviors. It is therefore important to take into account the individual tumor behavior when one is planning a proper surgical treatment. The behavior of the tumor governs the required surgical treatment which may range from simple curettage of the tumor to radical resection of the jaw.